2008
DOI: 10.1111/j.1533-2500.2008.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Residual Limbs of Amputees Are Significantly Cooler than Contralateral Intact Limbs

Abstract: DRLs as measured by qIRT were significantly cooler than the corresponding area of the contralateral intact limbs. A better understanding of these findings may be important in elucidating the pathophysiology of relevant clinical features such as a potential sympathetic component of postamputation pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 23 publications
5
24
1
Order By: Relevance
“…PTC and skin temperature may differ in diabetic patients because of peripheral nerve dysfunction and reduced blood flow, with supportive evidence that the most pronounced sensory deficit in the diabetic foot is elevated cold perception test scores [22]. Although no difference in residual limb temperature was found in a study of those with dysvascular (n = 10) versus traumatic (n = 21) amputation [7], additional study of skin temperature and PTC using larger samples of participants with diabetic versus traumatic amputation is warranted. Additionally, we intended to measure four distinct thermistor locations on the residual limb.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…PTC and skin temperature may differ in diabetic patients because of peripheral nerve dysfunction and reduced blood flow, with supportive evidence that the most pronounced sensory deficit in the diabetic foot is elevated cold perception test scores [22]. Although no difference in residual limb temperature was found in a study of those with dysvascular (n = 10) versus traumatic (n = 21) amputation [7], additional study of skin temperature and PTC using larger samples of participants with diabetic versus traumatic amputation is warranted. Additionally, we intended to measure four distinct thermistor locations on the residual limb.…”
Section: Discussionmentioning
confidence: 97%
“…Prior work demonstrated that while standing for at least 15 min without a prosthesis at room temperature, the residual limb skin temperature of participants with amputation was on average 1°C cooler than the contralateral limb [7]. After donning a prosthesis and resting for 15 min, residual limb skin temperatures increased by just under 1°C, with further increases after 10 min of slow walking at room temperature [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several articles in the literature report an abnormal sympathetic [1,3,5] and parasympathetic [21] activity in the residual-limb region, even without reporting PLP [4]. Therefore, it seems that PLP is not a condition for developing abnormalities in ANS function.…”
Section: Discussionmentioning
confidence: 98%
“…Among all the causes hypothesized as triggers of PLP, one relates to the autonomic nervous system (ANS). This cause is based on abnormal sympathetic activity on the residual limb, which affects sympathetic-efferent outflow of cutaneous vasoconstrictor fibers, skin temperature, and sympathetic impulse pattern [1,[3][4] even in subjects without pain [4]. Moreover, Katz reports that increases in the intensity of PL paresthesiae follow bursts of sympathetic activity in the residual-limb neuromas while decreases correspond to periods of relative sympathetic activity [1].…”
Section: Introductionmentioning
confidence: 99%